"I Would Not Consider Myself a Homophobe": Learning and Teaching About Sexual Orientation in a Principal Preparation Program. (August 2013) - Marshall, Joanne M.; Hernandez, Frank
Purpose: The purpose of this study is to analyze the written reflections of aspiring principals in two principal-preparation courses where social justice is at the core of the content and which address sexual orientation as part of the responsibility of a social justice leader.Data Collection: Two instructors in a leadership-preparation program incorporated reflection assignments into their respective social-justice-related courses. One course was offered at the beginning of the program; the other offered at the end. Aspiring principals from two different cohorts of students participated in the study. The students' reflections were coded to identify themes and patterns that were found in their reflections and to see if any of their reflections changed over time.Findings: The authors found that students had varied experiences with people who identified as LGBTQ. Second, we found that discussion of sexual orientation was complicated by students' Christian beliefs. Third, we found that there was some change in the way in which students responded to sexual orientation, from a more passionate to a more analytical stance. We discuss these findings in light of the need for better assessment of future leaders' attitudes and actions and of our own heteronormativity and heterosexism. We discuss implications for our own teaching as well as for other teachers in preparation programs.